2011
DOI: 10.5172/conu.2011.206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different bed support surface covers on skin temperature

Abstract: The type of support surface protector material greatly influences skin temperature depending on the specific area of the body in contact with the surface. The protective plastic that is currently used in hospitals may increase the risk of skin lesions. Simple changes in practices could help minimize the negative impact that plastic protectors contribute to the skin. Regardless, the surface area should be covered with protective covers that do not produce an increase in local temperature and hygienically mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It is well known that the water transport and thermo‐mechanical properties of the material of the cover and/or textile have an impact on the local water accumulation during loading. Layers of linens or underpads on mattresses could reduce the ability to transport heat and evaporate moisture .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the water transport and thermo‐mechanical properties of the material of the cover and/or textile have an impact on the local water accumulation during loading. Layers of linens or underpads on mattresses could reduce the ability to transport heat and evaporate moisture .…”
Section: Discussionmentioning
confidence: 99%
“…PU prevention support surfaces affect the microclimate as well and, thus, the skin . The construction and material of the support surfaces (eg, foam vs low‐air‐loss) or the cover type are key predictors for temperature and humidity between the skin support surface interface . The interaction between skin function and fabrics (eg, bed sheets, clothing) is also well known .…”
Section: Introductionmentioning
confidence: 99%
“…Relative skin temperature change was found to increase 2.4 °C in both mattresses. Lying supine on the mattress was found to raise skin temperature by 2-3 °C, approaching the body's core temperature [16]. In our experimental protocol, both mattresses were covered with an identical standard mattress cover.…”
Section: Discussionmentioning
confidence: 94%
“…Prolonged sitting leads to the increased potential for skin maceration because of humidity build up [2][3][4][5] and increased friction between the person and seat or support surface [6][7][8][9][10][11] consequently skin damage is more likely. Some studies have indicated that body humidity could be an important property to investigate in order to understand the microclimate of the sitting interface between a person and seat surface [3,4,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%